PRINCIPLES AND ALGORITHMS OF ETHICAL ADVOCACY IN THE GLOBAL MEDIA SPACE: AN AXIOLOGICAL-COMMUNICATIVE MODEL - Turayev, Kamoliddin Samadovich (Oriental Journal of History, Politics and Law, 2026)
The article examines the legitimate boundaries, value principles, and algorithmic mechanisms of ethical advocacy in the global media space. The research problem arises from the risk that the promotion of socially beneficial ideas may turn into manipulative communication through personalization, emotional amplification, and hidden audience segmentation. The study aims to distinguish ethical advocacy from coercive propaganda and to develop an integrated model for content creation and algorithmic distribution. Dialectical, axiological, comparative, systemic-functional, hermeneutic, and content-analysis methods were employed. The findings provide an operational definition of ethical advocacy, systematize seven principles, and introduce the nine-stage “ETIK-MEDIA” algorithm and a 100-point Ethical Advocacy Responsibility Index. The novelty lies in integrating the value content of a message with the method of influence, algorithmic amplification, transparency, user autonomy, and appeal mechanisms within one assessment framework. The model can serve as an ethical review tool for newsrooms, public and civil-society communication institutions, digital platforms, and media literacy programmes.